SOME ISSUES OF IMPROVING THE ANALYSIS OF THE FINANCIAL STATUS OF ENTERPRISES - Khudayberdiev Bakhtiyorjon Maribjon ugli (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article explores the methodological aspects of improving the analysis of the financial condition of economic entities on the example of railway transport enterprises. The article analyzes the factors influencing the financial situation, using the example of passenger transportation, provides scientific proposals and practical recommendations necessary for making effective management decisions.